2015
DOI: 10.4103/0972-3919.159693
|View full text |Cite
|
Sign up to set email alerts
|

Dual time point fluorodeoxyglucose positron emission tomography/computed tomography in differentiation between malignant and benign lesions in cancer patients. Does it always work?

Abstract: Objectives:Assess the added value of dual time point F-18-fluorodeoxyglucose positron emission tomography/computed tomography (DTP F-18-FDG-PET/CT) in the differentiation of malignant from a benign lesion in cancer patients.Materials and Methods:Totally, 140 F-18-FDG PET/CT scans of 60 cancer patients who underwent DTP protocol (early whole body PET/CT [E] at 60 min [range, 45–76 min] and delayed limited PET/CT [D] on areas of interest at 120 min [range, 108–153 min] after the tracer injection) were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Like the results of previous studies, almost all lesions showed higher FDG uptakes during the delayed phase, compared to the early phase, in our study. Not SUV max but ΔSUV max was significantly associated with both PFS and OS in a univariate analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Like the results of previous studies, almost all lesions showed higher FDG uptakes during the delayed phase, compared to the early phase, in our study. Not SUV max but ΔSUV max was significantly associated with both PFS and OS in a univariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…According to some previous studies that evaluated dual‐time‐point FDG‐PET/CT, malignant tumors generally exhibit enhanced FDG uptake during the delayed phase, compared with the early phase . In contrast, physiological FDG uptake is known to decrease over time after FDG injection .…”
Section: Introductionmentioning
confidence: 99%
“…But dual time point imaging did not always work in differentiation between benign and malignant lesions. [ 13 ] Choi et al reported that dual time point imaging did not improve the overall performance of 18 F-FDG PET/CT in detecting axillary lymph node metastasis in breast cancer patients. [ 14 , 15 ] In principle, RI is a useful index because it has a merit of not being dependent on scale.…”
Section: Discussionmentioning
confidence: 99%
“…In our subgroup analysis, the quantitative analysis based on SUVmax displayed a much higher sensitivity than qualitative analysis (0.84 vs. 0.47), with the imaging analysis being regarded as a potential resource of heterogeneity in our meta-analysis [ 54 ]. In fact, a lack of unified criteria prevents confirmation of the diagnosis of lymph node metastasis and the cutoff values of SUVmax differing in quantitative analysis [ 54 , 81 , 82 ]. When coupled with the long scanning-acquisition time and expense, 18 F-FDG PET/CT is not recommended as the first choice for clinically assessing lymph node staging in GC patients [ 38 , 41 , 80 ].…”
Section: Discussionmentioning
confidence: 99%